ORGANIZATIONAL’S IMPROVEMENT OF PRODUCER’S ASSOCIATION OF ORGANIC PRODUCTION IN REPUBLIC OF MACEDONIA - Hadzi Naumova-Mihajlovska, Katerina (Institute of Economics - Skopje, 2015)
Total quality management (TQM) have proven very valuable to companies and organizations as an integrative approach anchored in the belief that long-term success depends on unique commitment to quality in all departments of an organization. One important approachin agriculture whose base is the commitment to qualityin all phase of working and production is organic agriculture. Republic of Macedonia is not lagging behind in development of organic agriculture, but the producers are facing problems such as poor market organization and insufficient quantity of products for sale.The paper attempts to show that TQM can improve the organization of producer’s associations of organic products with “continuous improvements” as a strategy for the competitive position and improvement in organizing.
Keywords: TQM, continuous improvement, associations,organic production, Republic of Macedonia.